The Political Powers of the State in the New Constitution - Rubio Correa, Marcial (1981)
The previous Constitution of 1933 reflected severe limitations in resolving conflicts between state organs. Consequently, it is important to examine the modifications implemented by the new constitution. Only in this way will it be possible to evaluate to what extent the changes affected or not the dynamics between the political powers that make up the State. In this sense, this article analyzes the interrelationship between the Executive and Legislative branches in the Peruvian Constitution of 1979. After addressing the determining aspects of the subject, the author concludes by pointing out that the reforms introduced by the new Magna Carta are partial and do not contribute to an adequate system of checks and balances; which ends up affecting the balance between the political powers of the State. Therefore, it is recommended to aim for a deeper restructuring that improves the efficiency of the political system.